L-lactate exerts a pro-proliferative effect on adult hippocampal precursor cells in vitro - Pötzsch, Alexandra (iScience, 2021)
L-lactate has energetic and signaling properties, and its availability is modulated by activity-dependent stimuli, which also regulate adult hippocampal neurogenesis. Studying the effects of L-lactate on neural precursor cells (NPCs) in vitro, we found that L-lactate is pro-proliferative and that this effect is dependent on the active lactate transport by monocarboxylate transporters. Increased proliferation was not linked to amplified mitochondrial respiration. Instead, L-lactate deviated glucose metabolism to the pentose phosphate pathway, indicated by increased glucose-6-phosphate dehydrogenase activity while glycolysis decreased. Knockout of Hcar1 revealed that the pro-proliferative effect of L-lactate was not dependent on receptor activity although phosphorylation of ERK1/2 and Akt was increased following L-lactate treatment. Together, we show that availability of L-lactate is linked to the proliferative potential of NPCs and add evidence to the hypothesis that lactate influences cellular homeostatic processes in the adult brain, specifically in the context of adult hippocampal neurogenesis.